Effect Debt Policy On Profitability, And Dividend - Irza Shara Hervina (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to examine the phenomenon of debt in state enterprises (BUMN) which is excessive without being followed by an increase in profitability. The sample used is state-owned enterprises (BUMN), the various business sectors for the 2015-2018 period. Using purposive sampling got 137 samples and data processing using the IBM SPSS series 23 program. The result is that debt policy has a negative impact on profitability; it does not prove liquidity to affect profitability. It does not prove liquidity to determine dividends. Debt policy has a negative effect on dividends, and profitability has a positive effect on dividends.